FLUID INCLUSIONS AND THEIR STABLE ISOTOPE GEOCHEMISTRY OF THE CARBONATE-HOSTED TALC DEPOSITS NEAR THE CRETACEOUS MUAMSA GRANITE, SOUTH KOREA - Shin D.; Lee I. (My University, 2006)
Microthermometric and stable isotope studies of fluid inclusions were conducted for the Poongjeon talc deposit which formed as alteration products of calc-silicate minerals during the retrograde stage of contact metamorphism related to the intrusion of the Cretaceous Muamsa Granite of South Korea. Two types of quartz vein are observed in the deposit. Vein I, which occurs in marble, is characterized by both mixing and unmixing process of fluid inclusions. Repeated boiling of carbonic fluids produced high XCO2 fluids abundantly and low XCO2 or aqueous fluids a little. Occasionally mixing took place between halite ± sylvite-bearing fluids and carbonic fluids. As for vein II, which occurs typically at points of amphibolite-metapelite contact, the fluid mixing model can be applied to the coexistence of abundant CH4 ± H2O, H2O-CO2-CH4 fluids with variable CH4/CO2 ratios (XCH4 > 0.1), and minor high XCO2 fluid inclusions. The CH4-rich inclusions seem to be derived from the reheating of C-bearing metapelite during contact metamorphism. Occurrences of halite ± sylvite-bearing inclusions along traits in both vein I and II are chronologically behind other primary inclusions and are closely related to the talc mineralization. The mineralizing fluids would have been derived directly from a water-saturated crystallizing melt and the entrapment occurred between 150 and 700 bars at 260°-390°C. The δ13CCO2 values, 0.1-2.4‰, of inclusion fluids of vein I seem to have resulted from the isotopic exchange of magmatic carbon with 13C-enriched CO2 liberated from the decarbonation for calc-silicate formation. Distinctly lower δ13CCO2 values, -3.5 to -1.7‰, in vein II could have originated from the strong effect of metasediment-derived fluids. Higher δ18OH2O values of vein I and lower δD values of vein II, both of which belong to the magmatic water range, seem to have similar evolution history as δ13C values. Geologic structures such as faults and contacts between different rock units seem to have promoted infiltration, mixing, and unmixing of fluids of diverse origins. Copyright © 2006 by The Geochemical Society of Japan.
Keywords: FLUID MIXING; SOUTH KOREA; STABLE ISOTOPE; TALC DEPOSIT; UNMIXING; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая